AI-Edmodo E-Learning in Physics Learning: A Study of Students' Cognitive Ability on the Topic of Work and Energy - Tuhurima, David; Batlolona, John Rafafy; Wenno, Izaak Hendrik (STKIP Singkawang, 2025)
Teachers have used various ways to explore innovative learning to improve students' cognitive physics skills. Edmodo is a free and secure educational learning network that provides a simple way for teachers to create and manage online classroom communities. This study aimed to analyze the effect of the Edmodo application in improving students' cognitive abilities in physics on the topic of work and energy. The analysis of this study focused on cognitive abilities and student motivation in the classroom. The method used in this research is a quasi-experiment with a pretest-posttest design using descriptive research type that aims to describe the situation/symptom or phenomenon, which is designed to obtain information in the current state. In this case, the improvement of students' cognitive abilities can be seen by using the Edmodo application. The research design used is One Group Pretest-Posttest Design. The sample in this study was class 10 in the Science department, with a total of 27 students using a random sampling technique. Data collection was done by using a physics cognitive ability test. Quantitative data of this study were obtained through objective tests (pretest-posttest) based on Bloom's Taxonomy. The results of this study indicate that the application of Edmodo can improve students' cognitive abilities in physics. With the increase in students' physics cognitive abilities in learning, the learning outcomes of previously low students increased significantly. Therefore, it is recommended that AI-Edmodo improve students' physics cognitive abilities in learning physics on the topic of work and energy.